Climate Change: Could State Sovereignty Over Maritime Boundaries Also Change? - Ardianto, Budi; Helmi, Helmi; Putra, Akbar Kurnia; Munawir, Munawir; Hardyanthi, Try (Uti Possidetis: Journal of International Law, 2026)
Background: Climate change has presented a serious challenge to traditional concepts of state sovereignty in international law, particularly in the context of establishing baseline as the basis for measuring maritime boundaries. Sea level rise that causes the sinking of small islands and the shift of coastline has the potential to change the delimitation of a country's maritime area, thereby creating uncertainty over the scope of maritime sovereignty. However, the 1982 United Nations Convention on the Law of the Sea (UNCLOS) does not explicitly regulate the mechanism for adjusting the baseline due to such permanent geographical changes. Based on these conditions. Methodology: This study uses normative juridical methods with a legislative, conceptual, and analytical approach to the practice and development of international law. Objective: This study aims to analyze whether and how state sovereignty over marine areas can be maintained when the geographical basis of determining the baseline changes due to climate change. Findings: The results of the analysis show that the application  of the concept of fixed baseline or historical baseline can be a relevant legal instrument to maintain stability, legal certainty, and sustainability of maritime sovereignty of archipelagic countries. Originality: The uniqueness of this research lies in the effort to reconstruct the concept of state sovereignty in international law of the sea through a non-ambulatory approach to the baseline as a normative response to climate change, by placing the interests of archipelagic countries such as Indonesia as the focus of the analysis.